"Better Than Bank Robbery": Yuezi Centers and Neoliberal Appeals to Market Birth Tourism to Pregnant Chinese Women. Issue 4 (3rd April 2018) - Ji, Yadong; Bates, Benjamin R.
ABSTRACT: "Birth tourism" has rarely been addressed by scholars. The ways that pregnant women are encouraged to leave their homelands and give birth abroad have not been investigated. Birth tourism agencies may seek to persuade women that particular destinations—such as the US—are ideal places for giving birth. An examination of how birth tourism agencies frame birth tourism may offer initial insights into this phenomenon. This study examines 34 agencies' home pages and their arguments advocating birth tourism for Chinese expectant mothers. Using a thematic approach, we find four reasons offered to pregnant Chinese women that make birth tourism appealing. This perspective helps us to understand birth tourism both as a health-related behavior and a cosmopolitan issue. We use neoliberalism as an analytic framework to examine how birth tourism may enhance inequality in health resource distribution both domestically and internationally.